On-site greywater treatment systems - influent and effluent quality - Sami, Mashreki; Hedström, Annelie; Kvarnström, Elisabeth; Herrmann, Inga (Luleå University of Technology, 2023)
The dataset presented here consists of raw data on the quality of influent and effluent greywater from eight on-site greywater treatment systems situated in Södertälje municipality, Sweden. These on-site treatment systems included three types of commercially available package plants and one sand filter. The influent and effluent samples were taken as grab samples between August 2020 and December 2021 and analysed for organic material, nutrients, pathogens, anionic surfactants, salt and (for two of the eight on-site systems) microplastics. Supporting parameters, e.g. suspended solids and pH, are also included. Further, for microplastics, results from blank samples are included.

This dataset was used to evaluate the treatment efficiency of the on-site greywater treatment systems and to assess the suitability of the treated water for reuse.

See the attached documentation files.
1. Study_Description: This file includes the summary of the research study, data collection and the standard analytical methods used for analyzing different parameters.
2. Greywater Characteristics: The influent and effluent concentrations of all parameters analyzed during all sampling events.

Datasammanställningen som presenteras här innehåller rådata från provtagningar som utfördes vid åtta enskilda anläggningar för behandling av bad-, disk- och tvättvatten (BDT) i Södertälje kommun. Prover togs från tre typer av minireningsverk och en markbädd för BDT rening. Stickprover togs från inkommande och utgående vatten mellan augusti 2020 och december 2021 och analyserades på organisk substans, näringsämnen, indikatorbakterier, anjoniska tensider, salt och (för två av anläggningar) mikroplast. Mätningar på andra parametrar såsom pH och suspenderat material är inkluderade. För mikroplast inkluderas dessutom resultat på blankprover.

Detta dataset har använts för att utvärdera reningseffektiviteten av de enskilda BDT-vattenanläggningarna och för att bedöma om det renade vattnet skulle kunna återanvändas.

Se bifogade dokumentationsfiler.
1. Study_Description: Detta dokument innehåller en sammanfattning av hur provtagningar och analyser utfördes.
2. Greywater Characteristics: Uppmätta koncentrationer i inkommande och utgående vatten vid de olika provtagningstillfällena.
Behandling av bad-, disk- och tvättvatten i enskilda avloppsanläggningar - Kvalitet på inkommande och utgående vatten
Keywords: water quality; vattenkvalitet; package plants; små reningsverk; matter; materia; phosphorus; fosfor; nitrogen; kväve; pathogens; patogener; greywater; gråvatten; surfactants; tensider; microplastics; mikroplaster; Infrastructure Engineering; Infrastrukturteknik; Environmental Engineering; Naturresursteknik; Water Treatment; Vattenbehandlingsbioteknik